World development report 1978. (World Development Report, 1978)
This first report deals with some of the major development issues confronting the developing countries and explores the relationship of the major trends in the international economy to them. It is designed to help clarify some of the linkages between the international economy and domestic strategies in the developing countries against the background of growing interdependence and increasing complexity in the world economy. It assesses the prospects for progress in accelerating growth and alleviating poverty, and identifies some of the major policy issues which will affect these prospects.